HUBUNGAN WORK ENGAGEMENT DENGAN KINERJA GURU DI MADRASAH ALIYAH NEGERI - Mulyani, Heny; Kartadiharja, Ricky Oka (Jurnal Isema : Islamic Educational Management, 2023)
One of the factors that influence teacher performance is work engagement. Work engagement or what is often referred to as work engagement is an important aspect of teacher performance in Madrasahs. Work engagement is characterized by Vigor, Dedication, and Absorption. The method used in this study is descriptive, using a quantitative approach to the correlation type. The results of the research show that there is a relationship between Work engagement and Teacher Performance in State Madrasah Aliyah throughout Bandung Regency, with a significance value of 0.001. 0.000 <0.05 means that there is a correlation or relationship between work engagement and teacher performance